Factors Influencing Pricing Decisions of Customers in the Medical Device Industry Across Geographies - Gupta, Mayank (Digital Repository of Theses, 2024)
Pricing is one of most important yet neglected marketing fundamentals in the healthcare industry. With the help of the price optimization, many organization can improve their revenues and profitability. With home care medical device industry growing a rapid rate, it is important for the business to understand how to optimize the prices using different factors. While pricing a product, many internal factors like product cost, company vision, company’s focus on the current and next financial year and objectives they are trying to achieve from a product or product category are considered while ignoring the consumer behavior aspect. The consumer behavior varies by geographies; hence the research is conducted for multiple countries and considering important consumer behavior factors to have a comparative analysis and provides the global vision to the organization. The study uses the quantitative methods which provides insights on the importance of the various factors which are forming the decision-making process of the customers while purchasing a medical device like blood pressure monitoring system, blood sugar detection devices and oximeter. The analysis also helps in understanding the psychological and discount behavior of the customer. There are 23 hypotheses created for the study and are validated with the data generated for 5046 respondents. The data is analyzed using statistical measures like ANOVA and regression to understand the importance and influence of various factors and quantifying the decisions to understand the improvement in their profitability. The findings from the study are helpful for small as well as large organization. It will also be helpful to the new entrants for the home health care industry. The results can be used to understand the impact to their business if they target different demographics and other key factors, they need to work to influence their respective consumers. The results and insights generated can be used by the business and organization in their pricing strategy, digital marketing and positioning their product.